1996
DOI: 10.1017/s0952523800008233
|View full text |Cite
|
Sign up to set email alerts
|

GABAB-receptor-mediated inhibition reduces the orientation selectivity of the sustained response of striate cortical neurons in cats

Abstract: Blocking GABAA-receptor-mediated inhibition reduces the selectivity of striate cortical neurons for the orientation of a light bar primarily by reducing the selectivity of their onset transient (initial 200 ms) response. Blocking GABAB-receptor-mediated inhibition with phaclofen, however, is not reported to reduce the orientation selectivity of these neurons when it is measured with a light bar. We hypothesized that blocking GABAB-receptor-mediated inhibition would instead affect the orientation selectivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…2D, which plots a time-resolved DI for the population response in the presence and absence of BMI. These findings imply that, in a subset of neurons, directional tuning during the early response period is substantially shaped by inhibition mediated through GABA A from within MT whereas, during late-response periods, either afferent inputs supply the directional information or inhibitory mechanisms other than GABA A participate in its generation (25). This finding contradicts a strictly hierarchical view in which directional tuning is simply inherited from earlier stages (13) and where MT neurons perform more complex and global computations about object and͞or ego-motion (13,26).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…2D, which plots a time-resolved DI for the population response in the presence and absence of BMI. These findings imply that, in a subset of neurons, directional tuning during the early response period is substantially shaped by inhibition mediated through GABA A from within MT whereas, during late-response periods, either afferent inputs supply the directional information or inhibitory mechanisms other than GABA A participate in its generation (25). This finding contradicts a strictly hierarchical view in which directional tuning is simply inherited from earlier stages (13) and where MT neurons perform more complex and global computations about object and͞or ego-motion (13,26).…”
Section: Resultsmentioning
confidence: 90%
“…It is interesting to note that BMI mostly affected the early-response period whereas later periods show stronger directionality, even in the presence of BMI. A study on the contribution of GABA A vs. GABA B in shaping tuning functions has demonstrated that GABA A mostly influence the early-response component whereas the sustained response is mostly affected by GABA B (25). Based on these findings, it is tempting to speculate that neurons that are nondirectional during their earlyresponse period in the presence of BMI (a GABA A antagonist) might not regain their directionality during later response periods if baclofen (a GABA B antagonist) was also applied.…”
Section: Resultsmentioning
confidence: 99%
“…We conclude that cortical GABA A inhibition plays a minor role in the suppressive effect of the CRF surround. However, there is a report that a blockade of GABA B receptors in V1 reduces the orientation selectivity of the sustained component of visual response (Allison et al, 1996). Therefore, the contribution of slow GABA B inhibition to surround suppression remains to be clarified.…”
Section: Blockade Of Inhibitory Synapses By Iontophoretically Adminismentioning
confidence: 99%
“…There is ample evidence that GABAB receptors mediate slow IPSPs following the electrical stimulation of afferents to LGN X and Y cells in vitro (Soltesz, Lightowler, Leresche & Crunelli, 1989) but there have been few attempts to ascribe a function in visual processing to GABAB receptors. One recent report (Allison, Kabara, Snider, Casagrande & Bonds, 1996) suggests that GABAB receptors participate in the generation of orientation tuning in conjunction with GABAA receptors in the visual cortex. The finding that GABAB receptors are involved in response habituation is quite novel.…”
Section: The Effects Of Gabaergic Agonistsmentioning
confidence: 99%